EFEKTIFITAS PENGEMBALIAN MODAL USAHA KELOMPOK DALAM PROGRAM PENGEMBANGAN USAHA AGRIBISNIS PEDESAAN (PUAP) DI DESA KUALU NENAS KECAMATAN TAMBANG KABUPATEN KAMPAR - Cepriadi '; Shorea Khaswarina; Lara Trisiana (Fakultas Pertanian, Universitas Riau, 2011)
The purpose of this research is to 1) analyze the disbursement of credit fund from RuralAgribusiness Development micro finance (PUAP) and 2) to analyze the effectiveness ofloan repayment from group of farmers (Gapoktan) in Kuala Nenas village District ofTambang, Kampar Regency. This research was carried out for 3 months from Octoberuntil December 2010. This research found that the credit fund was distributedappropriately to eligible farmers. Meanwhile the rate of return or repayment of loan ingeneral was also good, in other word the non performing loan is only small in term ofthe amount of money and in the number of farmers.Keyword: capital distributing process, capital returning effectivenes, PUAP program’s